Influence of gamma rays on the physico-chemical, release and antibacterial characteristics of low-density polyethylene composite films incorporating an essential oil for application in food-packaging. (March 2019) - Swilem, Ahmed E.; Stloukal, Petr; Abd El-Rehim, Hassan A.; Hrabalíková, Martina; Sedlařík, Vladimír
Graphical abstract: Highlights: An antimicrobial essential oil was loaded into wood flour or molecular sieves and then thermally incorporated into LDPE. The release of essential oil was slower in composites filled with wood flour. The composites were better at inhibiting the growth of the Gram-positive bacteria. Exposing the composites to gamma rays has beneficial effects in delaying the release of essential oil, particularly in case of composites filled with wood flour. Thermal and mechanical properties of the composites did not change significantly with irradiation. Abstract: We investigated the effect of gamma irradiation on the properties of low-density polyethylene composite films incorporated with the antimicrobial terpene 4-allylanisole (ALY), and the volatile release of ALY. For comparison, wood flour and molecular sieves were used as solid carriers for ALY at loading ratios of 20 and 30 wt.%. Infrared spectroscopy indicated that a proportion of ALY underwent structural change during melt-compounding and irradiation at high doses (> 10 kGy). Thermal and mechanical properties of composites prepared did not alter remarkably after irradiation. The release study of ALY showed that using wood flour and irradiation reduced the volatilization of ALY from the polymer matrix; however, the effect exerted by irradiation treatment was less noticeable than that of the carrier type. The antibacterial activity study demonstrated that irradiation only exerted a pronounced negative effect on samples that contained 30 wt.% of ALY/wood flour when irradiated at 30 and 50 kGy.